Four new species of the genus Eusterinx Förster, 1869 (Hymenoptera, Ichneumonidae, Orthocentrinae) from Burundi and Kenya - Varga, Oleksandr (Zootaxa, 2026)
In this paper, four new African species of the genus Eusterinx Förster, 1869 are described: E. kibira sp. nov. from Burundi; E. elgonensis sp. nov., E. kenyaensis sp. nov., and E. pyramidalis sp. nov. from Kenya. Eusterinx africana Humala, 2024 is recorded from Kenya for the first time.